VORTEX DEVICES OF THE DIESEL AIR SUPPLY SYSTEM: MATHEMATICAL MODEL OF AERODYNAMIC PROCESSES - R. V. Yakimushkin (Вестник СибАДИ, 2020)
Introduction. The calculation of effective indicators of the vortex ejector used in the diesel air supply system is a pressing task as it allows significantly reducing time for determination of rational design parameters at the design stage. One of the modifications of the particle dynamics method is a promising direction, allowing with high physical adequacy, “from the first principles,” to model aerodynamic processes in vortex devices. Therefore, the purpose of the paper is to develop a mathematical model of a vortex ejector.Materials and methods. The paper discussed a method of the mathematical simulation of ejection and ejection flows in a vortex ejector. The proposed modification of the particle dynamics method allowed describing aerodynamic processes with the help of simple laws of classical dynamics, and modeling them with the help of software of the Delphi 7 System. The author presented differential equations, which were solved by the Runge-Kutt method of the second order. As a result of the solution, the authors determined paths of air elements movement in the vortex ejector, which allowed estimating effective parameters of vortex devices.Results. To study the model, the author developed a program with the possibility to set geometric parameters of the vortex ejector in the interface window and to display the current values of the process parameters.Discussion and conclusions. Proposed mathematical model and computer program make it possible to quantify efficiency of vortex devices at their design stage. The advantage of the proposed mathematical model lies in more accurate calculation of vortex flow parameters from the vortex ejector design and physical properties of ejecting and ejecting flows.Financial transparency: the author has no financial interest in the presented materials or methods. There is no conflict of interest.